Digital Health Interventions for Parental Engagement in Early Childhood Nutrition and Feeding: A Review (International Journal of Applied Research and Innovation, 2026)
This review synthesizes global empirical evidence regarding digital health interventions designed to optimize parental engagement within early childhood nutrition and feeding frameworks. By systematically analyzing diverse modalities such as mobile applications, specialized websites, text messaging platforms, and interactive social media, the synthesis characterizes parental involvement patterns across multi dimensional behavioral trajectories and exposure frequencies. The extracted findings indicate that although advanced digital architectures successfully deliver tailored educational resources and evidence based behavior change mechanisms, sustaining active caregiver usage beyond initial uptake remains a critical challenge. Significant improvements in child dietary outcomes and parental responsive feeding practices are heavily concentrated within high active usage thresholds, whereas passive platform exposure yields minimal or transient behavioral shifts. Furthermore, intervention efficacy is strongly moderated by structural socio demographic variables, revealing profound equity divides where resource constrained families face heightened attrition driven by digital literacy limitations. Consequently, advancing pediatric nutritional health systematically necessitates a paradigm shift toward inclusive user centered architectures integrated within routine healthcare services to stabilize long term caregiver engagement across diverse populations.